If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 9 = 5y + -3y Reorder the terms: 9 + 3y = 5y + -3y Combine like terms: 5y + -3y = 2y 9 + 3y = 2y Solving 9 + 3y = 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 9 + 3y + -2y = 2y + -2y Combine like terms: 3y + -2y = 1y 9 + 1y = 2y + -2y Combine like terms: 2y + -2y = 0 9 + 1y = 0 Add '-9' to each side of the equation. 9 + -9 + 1y = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 1y = 0 + -9 1y = 0 + -9 Combine like terms: 0 + -9 = -9 1y = -9 Divide each side by '1'. y = -9 Simplifying y = -9
| -2n+6n=16 | | -1.4=2x | | 25x^2+10x+-8= | | 8D=5F | | -8(3b+4)+(25b-5)=0 | | -6f+13=2f | | 5+4(3x-8)-2(x+6)=x-9 | | 8n+22=-2(-4n+3)+7n | | r+8.4=-0.5 | | 6=-3(r+2) | | w^2+2w=99 | | 4a=a-18 | | 2=2x-6 | | -3n+30=-6(6+6n) | | 3x^3+25=x^2+75 | | 13=3n+6-8 | | 8b-12b+10b= | | x^2+3x-72=4x | | 9l=3l+3m | | 0.66X-16=0 | | 6(w-1)=3(w+5) | | 26-5x=-7(x-4) | | (-8y-5)(7y)*y=-3 | | 5p+2=11+4p | | 57=-7(7b-3)-(7-6b) | | 6x+6=3x | | 26-5x=-7-3r | | 4(u-4)-6u=4 | | 20-4(2w+1)=6w-4(6+w) | | (-8y-5)(7y)y=-3 | | 8c-3d=6 | | 1d+8=2d-17 |